Entrepreneurs of the future - Lazányi, Kornélia (Serbian Journal of Management, 2014)
Entrepreneurs are the gale of creative destruction. They are the engines of the local economy and contribute to a country’s wealth to a great extent. Accordingly it is of utmost importance, to create – educate and motivate – young adults to become entrepreneurs and start their own enterprises. The article summarises the basic facts about the Hungarian entrepreneurs’ and small and medium sized companies’ significance, and introduces a research on personal entrepreneurial competencies. The aim of the research is to explore the entrepreneurial potential of students in tertiary education, since they are the entrepreneurs of the future. In the research 470 young adults’ (students of tertiary education) responses are compared with those of successful entrepreneurs. According to the results successful Hungarian entrepreneurs produced better results on the personal entrepreneurial competencies test, scoring in most cases higher than the members of the student sample. In addition to this, patterns based on age, gender and work experience could be identified.